Kinetics and thermodynamics of adsorption on hydroxyapatite of the [160Tb]terbium complexes of the bone-targeting ligands DOTP and BPPED - Rill, Christoph; Kolar, Zvonimir I; Kickelbick, Guido; Wolterbeek, Hubert Th; Peters, Joop A (Langmuir, 2009)
The temperature-dependent adsorption on hydroxyapatite (HAP) of the Tb complexes of two macrocyclic DOTA-like ligands containing HAP-binding phosphonate groups was studied by a radiotracer method using 160Tb as the label. One ligand (DOTP) contains four separate phosphonate groups, while the second ligand (BPPED) contains a single bisphosphonate group coupled via a phosphinate spacer group. The equilibrium isotherms were fitted by models according to Langmuir, Freundlich, Langmuir-Freundlich, Toth, and Dubinin-Radushkevich, with the Langmuir-Freundlich and the Toth models resulting in the best fits. These models take into account the energetic surface heterogeneity of HAP for the binding of the complexes, which was confirmed by the dependence of the reversibility of the adsorption on the complex concentration. The affinity of the Tb-BPPED complex toward the HAP surface was substantially higher than that of the Tb-DOTP complex. Thermodynamic parameters obtained from the temperature-dependence of the adsorption and the Van't Hoff relation showed that the adsorption of both complex types is endothermic and entropy-driven, due to dehydration of the complex and the HAP surface during adsorption. The kinetics of the adsorption were very fast, and of the tested models (pseudo-first-order, pseudo-second-order, intraparticle diffusion, and Elovich) only the Elovich model described the experimental data suitably. The activation energy of the adsorption was calculated by application of an Arrhenius-type relation, showing chemisorption for both complex types. Adsorption rates were reduced when HAP with larger particle size was used.